Water/rock interactions, chemical weathering and erosion, and supergene enrichment in the Tapira and Catalão I alkaline‑carbonatite complexes, Brazil - Conceição, Fabiano T. da[UNESP] (2022)
Alkaline‑carbonatite complexes from the Alto Parnaíba Igneous Province (APIP) host important supergene concentrations of Nb, REE, P, and Ti. To quantify water/rock interaction and the interplay of chemical weathering and erosion that results in supergene enrichment, the chemistry of solutions draining the Tapira and Catalão I complexes were studied and the transfer of elements within and out of the weathering profiles quantified. Ca2+ and HCO3− are the main ions in surface water samples draining both watersheds, with an average annual flux of 49 t/km2/a of dissolved load. Total dissolved loads are highest during the summer (wet) months. The annual fluxes of Cl−, PO43− and NO3− yield negative values, suggesting significant input of these species from rainwater. The fluvial transport of dissolved elements due to silicate weathering, carbonate dissolution and rainfall input is ~26, 3 and 19 t/km2/a at Tapira and 29, 3 and 18 t/km2/a at Catalão I. Chemical weathering rates of alkaline rocks are ~4 m/Ma at Tapira and ~5 m/Ma at Catalão I. Constitutive mass balance suggests an eroded rock column of 84 m at Tapira and 39 m at Catalão I, with long-term erosion rates of 1.3 and 0.9 m/Ma, respectively. In contrast, long-term weathering rates were 3.0 m/Ma at Tapira and 2.4 m/Ma at Catalão I. Internal collapse of saprolites due to mass loss creates internal basins with an overburden of soils, locally transported material and lake sediments. Carbonate congruent dissolution, silicate incongruent dissolution and hydrolysis, and phosphate and oxide (pyrochlore) dissolution-reprecipitation are the main water/rock interactions in the Tapira and Catalão I alkaline‑carbonatite complexes that promote the enrichment of primary and secondary minerals and produce supergene P, Ti, Nb and REE deposits in the isalteritic saprolites; Ti is residually enriched in the alloteritic saprolite at Tapira.